Carbon and nitrogen isotopes to distinguish sources of sedimentary organic matter in a Caribbean estuary. Issue 5 (1st November 2020) - Alonso-Hernández, Carlos Manuel; Fanelli, Emanuela; Diaz-Asencio, Misael; Santamaría, Jesús Miguel; Morera-Gómez, Yasser
ABSTRACT: Carbon and nitrogen stable isotope compositions (δ13C and δ15N) of organic matter (OM) and total organic carbon to total nitrogen ratio (Corg/TN) in a sediment core collected in Sagua estuary (Cuba), were investigated to elucidate the origin of the Sedimentary OM (SOM) and changes in its main sources, over the last 100 years. Results showed almost constant values in the elemental and isotope composition of SOM from 1908 to 1970 with an abrupt change after 1970. From 1970 to 2005, δ13C increased from -21.2 up to -19.3 ‰, while δ15N declined from 1.5 to values close to 0 ‰. The output of the mass-balance model for the identification of OM sources indicated that δ13C and Corg/TN values are generally influenced by marine Particulate OM (POM) sources. Between 1900 and 1970, the main OM source in sediments was marine POM (>85 %), with freshwater POM contributing ca. 15%. Since 1970, the establishment of the Alacranes Dam determined drastic environmental changes influencing the OM sources in the area. Mixing models pointed to seagrasses (79 %) as the main contributors to SOM in the first period, while since 1973 onward, the contribution of human-derived sources such as fertilizers and urban discharges became greater. This information can provide baseline data for the environmental management of the Sagua watershed.